Heart failure and sleep‐disordered breathing: susceptibility to reduced muscle strength and preclinical congestion (SICA‐HF cohort). (23rd June 2020) - Bekfani, Tarek; Schöbel, Christoph; Pietrock, Charlotte; Valentova, Miroslava; Ebner, Nicole; Döhner, Wolfram; Schulze, P. Christian; Anker, Stefan D.; von Haehling, Stephan
ABSTRACT: Aims: Increased sympathetic activation in patients with heart failure (HF) and sleep‐disordered breathing (SDB) provokes cardiac decompensation and protein degradation and could lead to muscle wasting and muscle weakness. The aim of this study was to investigate the differences in body composition, muscle function, and the susceptibility of preclinical congestion among patients with HF and SDB compared with those without SDB. Methods and results: We studied 111 outpatients with stable HF who were enrolled into the Studies Investigating Co‐morbidities Aggravating Heart Failure. Echocardiography, short physical performance battery (SPPB), cardiopulmonary exercise testing, dual‐energy X‐ray absorptiometry, bioelectrical impedance analysis (BIA), tests of muscle strength, and polygraphy were performed. SDB was defined as apnoea/hypopnoea index (AHI) >5 per hour of sleep. Central sleep apnoea (CSA) and obstructive sleep apnoea (OSA) were defined as AHI >50% of central or obstructive origin, respectively. A total of 74 patients (66.7%) had any form of SDB [CSA (24 patients, 32.4%), OSA (47 patients, 63.5%)]. Patients with SDB showed increased muscle weakness (chair stand), reduced muscle strength, and lower values of SPPB score ( P  < 0.05). Patients with SDB did not show overt clinical signs of cardiac decompensation compared with those without SDB ( P  > 0.05) but had increased amounts of water (total body water, intracellular, and extracellular) measured using BIA ( P  < 0.05). Increased amounts of total body water were associated with the severity of SDB and inversely with muscle strength and exercise capacity measured by anaerobic threshold ( P  < 0.05). Altogether, 17 patients had muscle wasting. Of these, 11 (65%) patients had SDB (statistically not significant). Conclusions: SDB is highly prevalent in patients with HF. Patients with SDB have lower muscle strength and tend to be more susceptible to preclinical congestion.